2011
DOI: 10.1248/cpb.59.53
|View full text |Cite
|
Sign up to set email alerts
|

Three Steroids with Unique Structural Feature of 5.BETA.-Spirostan-1.BETA.,3.BETA.,17.ALPHA.-trihydroxyl from Reineckia carnea

Abstract: Regular ArticleReineckia carnea (ANDR.) KUNTH belongs to the family Liliaceae, it is the only species of the genus Reineckia and indigenous to China and Japan.1) As a perennial ever-green herb, it can grow well on soils polluted by heavy metals and can produce a repairing effect on the soil that was polluted by copper.2) The Chinese name "ji xiang cao" means it can bring luck and fortune to people, especially when it was cultivated as ornamental plant and flowers. The whole plant has been used as an antitussiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…A comparison of the NMR spectral data of 3 with those of 2 ( Tables 1 and 2) indicated that both compounds 3 and 2 were similar, except for the sugar residue linked to C‐9 of the aglycone. The signals from the sugar moiety, including 2 anomeric signals at δ 4.38 (d, J =7.1) and δ 5.20 (d, J =1.2) in the 1 H‐NMR spectrum and 11 carbons signals at δ 102.2, 77.8, 77.5, 70.1, 65.5 and δ 100.9, 70.9, 70.8, 72.6, 68.5, 16.5 in the 13 C‐NMR spectra were in agreement with those of published work [13–15] . Thus, the sugar unit was identified as α‐L‐rhamnopyranosyl‐(1→2)‐β‐D‐xylopyranosyl.…”
Section: Resultssupporting
confidence: 88%
“…A comparison of the NMR spectral data of 3 with those of 2 ( Tables 1 and 2) indicated that both compounds 3 and 2 were similar, except for the sugar residue linked to C‐9 of the aglycone. The signals from the sugar moiety, including 2 anomeric signals at δ 4.38 (d, J =7.1) and δ 5.20 (d, J =1.2) in the 1 H‐NMR spectrum and 11 carbons signals at δ 102.2, 77.8, 77.5, 70.1, 65.5 and δ 100.9, 70.9, 70.8, 72.6, 68.5, 16.5 in the 13 C‐NMR spectra were in agreement with those of published work [13–15] . Thus, the sugar unit was identified as α‐L‐rhamnopyranosyl‐(1→2)‐β‐D‐xylopyranosyl.…”
Section: Resultssupporting
confidence: 88%
“…(rha, C-3"), 74.5 (rha, C-4"), 69.9 (rha, C-5"), 18.8 (rha, C-6"). These data were identical with (1β,3β,5β,25S)-spirostan-1,3-diol1-[α-L-rhamnopyranosyl-(1→2)-β-D-xylopyranoside] [10] (Fig. 1A).…”
Section: Discussionsupporting
confidence: 76%
“…δ 6.8-14.4 for 5α-spirostane, δ 19.1-24.2 for 5β-spirostane) [7]. Different to 1, the broad singlet signal of H-1 (δ 3.92, brs) and H-3 (δ 4.40, br s) on the cis-fused A/B ring system were consistent with the 1β,3β-OH configuration [9]. In the NOESY plot, both H-3 and H-1 were correlated with α-oriented H-C (4) (δ 1.88), which was unambiguously assigned on the basis of the NOE correlation to H-C (9) (δ 1.35).…”
mentioning
confidence: 88%